1978
DOI: 10.1016/s0006-3495(78)85395-8
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies on viscoelastic properties of erythrocyte membrane

Abstract: The deformation of a portion of erythrocyte during aspirational entry into a micropipette has been analyzed on the basis of a constant area deformation of an infinite plane membrane into a cylindrical tube. Consideration of the equilibrium of the membrane at the tip of the pipette has generated the relation between the aspirated length and the dimensionless time during deformational entry as well as during relaxation after the removal of aspiration pressure. Experimental studies on deformation and relaxation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(195 citation statements)
references
References 18 publications
8
186
1
Order By: Relevance
“…Shear modulus of lipid bilayers is essentially zero due to its fluidity nature; shear modulus of RBC is mainly contributed from the spectrin network. The shear moduli of RBC membranes have been extensively measured by micropipette aspiration; the values for µ are in the range of 6-10 µ N/m (Evans and La Celle,1975;Chien, Sung et al,1978;Waugh and Evans,1979;Evans, Mohandas et al,1984). Techniques based on optial tweezers (Lenormand, Hénon et al,2001;Dao, Lim et al,2003), magnetic twisting cytometry (Puig-de-Morales- Marinkovic, Turner et al, 2007), and dynamic membrane fluctuation measurements have also reported consistent values for µ.…”
Section: Shear Modulusmentioning
confidence: 96%
See 1 more Smart Citation
“…Shear modulus of lipid bilayers is essentially zero due to its fluidity nature; shear modulus of RBC is mainly contributed from the spectrin network. The shear moduli of RBC membranes have been extensively measured by micropipette aspiration; the values for µ are in the range of 6-10 µ N/m (Evans and La Celle,1975;Chien, Sung et al,1978;Waugh and Evans,1979;Evans, Mohandas et al,1984). Techniques based on optial tweezers (Lenormand, Hénon et al,2001;Dao, Lim et al,2003), magnetic twisting cytometry (Puig-de-Morales- Marinkovic, Turner et al, 2007), and dynamic membrane fluctuation measurements have also reported consistent values for µ.…”
Section: Shear Modulusmentioning
confidence: 96%
“…where Rp is the radius of the micropipette, p is the applied pressure (Evans,1973;Chien, Sung et al,1978). Using micropipette aspiration, the value for µ was measured as 91.7 µN/m (Evans, Mohandas et al,1984).…”
Section: Micropipette Aspirationmentioning
confidence: 99%
“…The shear-thinning nature of blood has been tied to the disaggregation of the RBC-rouleau aggregates that form at low shear and the deformability of the RBCs (Chien et al, 1967a,b), while its stress-relaxation properties are tied to the viscoelastic nature of the RBC membrane (Evans and Hochmuth, 1976;Chien et al, 1978). The viscoelastic behavior of blood is less prominent at higher shear rates (Thurston, 1973).…”
Section: Whole Blood: Components and Rheological Behaviormentioning
confidence: 99%
“…In earlier studies, micropipette aspiration was performed either on liposomes 5 or on cells that were not attached to the substrate 2,[11][12][13] . In our studies, however, the cells are typically maintained attached to the substrate to avoid changes in the cytoskeletal structure that are likely to occur when cells detach [14][15][16] .…”
Section: Representative Resultsmentioning
confidence: 99%